1996
DOI: 10.1128/jvi.70.1.23-29.1996
|View full text |Cite
|
Sign up to set email alerts
|

Amino acids critical for the functions of the bovine papillomavirus type 1 E2 transactivator

Abstract: The N-terminal domain of the bovine papillomavirus type 1 E2 protein is important for viral DNA replication, for transcriptional transactivation, and for interaction with the E1 protein. To determine which residues of this 200-amino-acid domain are important for these activities, single conservative amino acid substitutions have been generated in 17 residues that are invariant among all papillomavirus E2 proteins. The resulting mutated E2 proteins were tested for the ability to support viral DNA replication, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
33
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 41 publications
3
33
0
Order By: Relevance
“…We expected to be able to determine what sequences in the activation domain of E2 were involved in interactions with E1. This expectation was based on results from several laboratories using various assays that indicated that the N-terminal portion of E2 was capable of interaction with E1 (4,7,22,35,38,39,59). Our data agree with the existence of an interaction domain in the N terminus of E2.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We expected to be able to determine what sequences in the activation domain of E2 were involved in interactions with E1. This expectation was based on results from several laboratories using various assays that indicated that the N-terminal portion of E2 was capable of interaction with E1 (4,7,22,35,38,39,59). Our data agree with the existence of an interaction domain in the N terminus of E2.…”
Section: Discussionsupporting
confidence: 85%
“…The interaction between the E1 and E2 proteins has several consequences, one of which is that the specificity of binding of the E1 protein to the ori is substantially increased. Furthermore, in the presence of E2, E1 binds to the ori in a form that in the absence of E2 lacks, or has very low, DNA binding activity, demonstrating that the interaction with E2 alters the DNA binding activity of the E1 protein (42).A number of studies have been performed to determine what regions in E2 are required for replication activity as well as for interactions with the E1 protein (4,7,14,17,22,35,38,39,50,56,58). The conclusion from these studies using a variety of methods all indicate that mutations in the N-terminal activation domain of E2 are deleterious for replication activity.…”
mentioning
confidence: 99%
“…Notwithstanding the HPV1a exception, as a general rule the E2 transactivator is required for viral DNA replication. Genetic analysis has localized determinants for replicative function within the N-terminal part of the BPV1 E2 molecule, a domain that is also required both for E1 binding and for transcriptional activation (1,5,13,15,16,57). Targeted mutagenesis has allowed us to clearly distinguish between these three functions, the binding of E1 being a likely prerequisite to the replicative function of E2.…”
mentioning
confidence: 99%
“…This N-terminal domain of E2 also functions as a transcription activation domain required for expression of the viral early genes (reviewed in reference 37). Although encoded by the same domain, the replication and transcription functions of E2 can be uncoupled by mutations (1,8,9,12,15,21,43). Recently, a 15-amino-acid peptide derived from HPV-16 E2 was shown to inhibit the interaction between E1 and E2 (25).…”
mentioning
confidence: 99%